Presenilin-1 280Glu-->Ala mutation alters C-terminal APP processing yielding longer abeta peptides: implications for Alzheimer's disease - Van Vickle, Gregory D. (2008)
Presenilin (PS) mutations enhance the production of the Abeta42 peptide that is derived from the amyloid precursor protein (APP). The pathway(s) by which the Abeta42 species is preferentially produced has not been elucidated, nor is the mechanism by which PS mutations produce early-onset dementia established. Using a combination of histological, immunohistochemical, biochemical, and mass spectrometric methods, we examined the structural and morphological nature of the amyloid species produced in a patient expressing the PS1 280Glu-->Ala familial Alzheimer's disease mutation. Abundant diffuse plaques were observed that exhibited a staining pattern and morphology distinct from previously described PS cases, as well as discreet amyloid plaques within the white matter. In addition to finding increased amounts of CT99 and Abeta42 peptides, our investigation revealed the presence of a complex array of Abeta peptides substantially longer than 42/43 amino acid residue species. The increased hydrophobic nature of longer Abeta species retained within the membrane walls could impact the structure and function of plasma membrane and organelles. These C-terminally longer peptides may, through steric effects, dampen the rate of turnover by critical amyloid degrading enzymes such as neprilysin and insulin degrading enzyme. A complete understanding of the deleterious side effects of membrane bound Abeta as a consequence of gamma-secretase alterations is needed to understand Alzheimer's disease pathophysiology and will aid in the design of therapeutic interventions.